Covid-19 Pandemic Moderating The Influence of Competence, Work Motivation and Entrepreneurship Orientation on Business Performance and Sharia Perspective - Sarwani, Sarwani; Suprihhadi, Heru; Feriswara, Dian; Lestari, Damajanti Sri; Listyawati, Liling (Universitas Islam Negeri Raden Intan Lampung, 2022)
The purpose of the article to analyze and empirically provethat the COVID-19 pandemic moderates the effect of competence, work motivation, and entrepreneurial orientation towards the business performance of SMEs. This study applies an explanatory approach to explain the causal relationship between variables through the hypothesis testing. Research data was collected by utilizing a questionnaire distributed to 130 SMEs and configured in 44 center groups in the city of Surabaya. Data analysis was conducted by Partial Least Square (PLS) approach.” Theresearch finding indicates that the COVID-19 pandemic as a moderating variable of the influence between variables. However, it turns out that not all the relationships regarding the COVID-19 pandemic are significant or strengthening.The empirical findings from the results of this study indicate that the COVID-19 pandemic has had a significant effect on competency, entrepreneurial orientation and business performance, as well as demonstrating the effect of entrepreneurial orientation on business performance.As for the effect of work motivation on entrepreneurial orientation and business performancehas an insignificant effect